2019
DOI: 10.3390/fermentation5030066
|View full text |Cite
|
Sign up to set email alerts
|

Mannoprotein Content and Volatile Molecule Profiles of Trebbiano Wines Obtained by Saccharomyces cerevisiae and Saccharomyces bayanus Strains

Abstract: : The production of volatile compounds has become one of the major technological features for yeast selection. In fact, although the aromatic profile of the wine is the sum of varietal-, pre-, post-, and fermentative-aroma compound, yeasts affect the quality of the grape from maturation throughout fermentation, metabolizing sugars and other components into alcohols, esters, organic acids, and aldehydes. Among the new technological features, the production of mannoproteins has gained interest. From this perspec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…However, the impacts of these genes in the production of MPs reported by researchers indicate that the modification of the culture conditions that influence the depression or overexpression of specific genes in certain yeasts could be considered to produce or release more MPs during the yeast cultivation (Gonzalez-Ramos et al, 2008;González-Ramos et al, 2010;Quirós et al, 2010). Except for the modern genetic method, traditional yeast-breeding methods including hybridization and mutagenesis were also found to be capable of breeding new types of yeasts that exhibited higher MPs production than their parental yeasts (Braschi et al, 2019;López-Malo et al, 2015;Pérez-Través et al, 2015) In recent decades, many researches have been conducted to explore the positive impacts of the non-Saccharomyces yeasts on wine quality, including their ability to improve wine aroma, stabilize wine pigments, and produce other metabolites that benefit wine quality (Casas-Godoy et al, 2021;Vejarano, 2020). Compared with the S. cerevisiae yeasts traditionally used in wine fermentation, one of the advantages many non-Saccharomyces yeasts exhibited during their growth was that they produced relatively higher amount of MPs (Table 5).…”
Section: Promising Raw Materials Rich In Mpsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the impacts of these genes in the production of MPs reported by researchers indicate that the modification of the culture conditions that influence the depression or overexpression of specific genes in certain yeasts could be considered to produce or release more MPs during the yeast cultivation (Gonzalez-Ramos et al, 2008;González-Ramos et al, 2010;Quirós et al, 2010). Except for the modern genetic method, traditional yeast-breeding methods including hybridization and mutagenesis were also found to be capable of breeding new types of yeasts that exhibited higher MPs production than their parental yeasts (Braschi et al, 2019;López-Malo et al, 2015;Pérez-Través et al, 2015) In recent decades, many researches have been conducted to explore the positive impacts of the non-Saccharomyces yeasts on wine quality, including their ability to improve wine aroma, stabilize wine pigments, and produce other metabolites that benefit wine quality (Casas-Godoy et al, 2021;Vejarano, 2020). Compared with the S. cerevisiae yeasts traditionally used in wine fermentation, one of the advantages many non-Saccharomyces yeasts exhibited during their growth was that they produced relatively higher amount of MPs (Table 5).…”
Section: Promising Raw Materials Rich In Mpsmentioning
confidence: 99%
“…However, the impacts of these genes in the production of MPs reported by researchers indicate that the modification of the culture conditions that influence the depression or overexpression of specific genes in certain yeasts could be considered to produce or release more MPs during the yeast cultivation (Gonzalez‐Ramos et al., 2008; González‐Ramos et al., 2010; Quirós et al., 2010). Except for the modern genetic method, traditional yeast‐breeding methods including hybridization and mutagenesis were also found to be capable of breeding new types of yeasts that exhibited higher MPs production than their parental yeasts (Braschi et al., 2019; López‐Malo et al., 2015; Pérez‐Través et al., 2015)…”
Section: Development and Application Of Mp Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in addition to the ability to produce specific volatile profile fingerprinting [49], some other technological features, such as the ability to release mannoprotein, could be a criterion of selection of S. cerevisiae strains in order to increase the molecule volatile profiles. In fact, mannoproteins, constituted by mannose (85-90%) and proteins (10-15%), in addition to some positive effects on the technological properties of wines (such as improving the wine colloidal stability, reducing the tannin self-aggregation preventing the reduction of the wine acidity, reducing the protein precipitation promoting the color stabilization), can also affect the release of volatile compounds, affecting the final perception of the wine [50]. In winemaking, the addition of commercial products rich in mannoproteins can be performed, but the challenge to find mannoprotein-producing yeast can represent a great advantage also from an economical point of view.…”
Section: Aldehydesmentioning
confidence: 99%
“…It has been shown that the use of mannoproteins (in low amounts) or the contact of the wine with fine lees increases the levels of esters (ethyl hexanoate, methyl, and ethyl hexadecanoate, which present fruity aromas), due to the esterification of fatty acids released during yeast fermentation or yeast autolysis [121,124], while higher amounts increase, in excess, fatty acid content, producing yeasty, herbaceous, and cheese-like smells [125]. However, it has been suggested that mannoproteins can be used to remove or reduce the incidence of wine off-flavors-4-ethylguaiacol and 4-ethylphenol.…”
Section: The Role Of Saccharomyces and Non-saccharomyces Mannoproteinmentioning
confidence: 99%